2005
DOI: 10.1007/s11240-004-2776-8
|View full text |Cite
|
Sign up to set email alerts
|

Polyacetylenes accumulation in Ambrosia maritima hairy root and cell cultures after elicitation with methyl jasmonate

Abstract: Three lines of hairy root culture of Ambrosia maritima induced by Agrobacterium rhizogenes ATCC15834 were established. Thiarubrine A, thiarubrine A epoxide, thiarubrine A diol and their precursor pentayneene were produced by the hairy roots after elicitation with methyl jasmonate, the common signal molecule in the plant defense and development. Thiarubrine A diol was the main form detected in the medium. Maximum yield was achieved when the 13-day-old hairy root cultures were exposed to 40 lM methyl jasmonate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
(15 reference statements)
3
10
1
Order By: Relevance
“…However, cell suspension cultures of L. erythrorhizon in M9 medium with addition of methyl jasmonate (50 lM) showed the content of ACS nearly two times higher than in the control (Gaisser and Heide 1996). The results of this study are in opposite to other investigations where methyl jasmonane has been found a very potent agent to enhance secondary metabolites production in hairy root cultures (Frankfater et al 2009;Kim et al 2009;Kittipongpatana et al 2002;Li et al 2005;Zid and Orihara 2005).…”
Section: Resultscontrasting
confidence: 88%
“…However, cell suspension cultures of L. erythrorhizon in M9 medium with addition of methyl jasmonate (50 lM) showed the content of ACS nearly two times higher than in the control (Gaisser and Heide 1996). The results of this study are in opposite to other investigations where methyl jasmonane has been found a very potent agent to enhance secondary metabolites production in hairy root cultures (Frankfater et al 2009;Kim et al 2009;Kittipongpatana et al 2002;Li et al 2005;Zid and Orihara 2005).…”
Section: Resultscontrasting
confidence: 88%
“…For hairy root cultures of Ambrosia maritima, the production of thiarubrine A (11Dj) and two derivatives was increased by methyl jasmonate [279]. In the presence of methyl jasmonate, cell suspension cultures only produced the biosynthetic precursor pentaynene 11E and at a level 9.6-fold lower than hairy roots.…”
Section: Use Of Higher Plant Cell Cultures To Study Polyacetylene Biomentioning
confidence: 99%
“…parthenemium roots (Stojakowska et al, 2002), and polyacetylenes were accumulated 72 h after treatment in Ambrosia maritima hairy root cultures (Zid and Orihara, 2005), which is similar to the time required to increase production of alkamides in our hairy root cultures. Similar results were obtained in Beta vulgaris, where high levels of MJ resulted in higher betalaine content after two weeks of culture (Suresh et al, 2004).…”
Section: Effect Of Chemical Elicitors On Root Growth and Alkamide Prosupporting
confidence: 73%
“…These results suggest that cultures should be challenged with the elicitor JA, when high availability of nutrients in the medium can be used for secondary metabolite biosynthesis (Zid and Orihara, 2005).…”
Section: Effect Of Chemical Elicitors On Root Growth and Alkamide Promentioning
confidence: 96%
See 1 more Smart Citation